Challenges and approaches towards upscaling the assembly of hybrid perovskite solar cells. Issue 3 (26th May 2020) - Shalan, Ahmed Esmail
Abstract : In the current review, we have reported the practical potential of PSCs, strategies, challenges, and approaches towards large-area scale PSC modules via different deposition techniques as well as functional materials for the device architecture. Abstract : In recent times, the next-generation photovoltaic technologies have accepted perovskite solar cells (PSCs) as different auspicious candidates as a result of their persistently developing efficiencies, thus attracting significant attention from both the scientific and industrial societies. Even though PSCs are dignified toward the commercial world through the photovoltaic module scale, significant challenges confusing industrialization remain. The recent efficiency of the solution-processed PSCs has reached over 25% on a laboratory scale. However, a reproducible allocation to the upscaling techniques of these processes still requires a highly controllable perovskite film formation strategy. Different coating systems such as blade coating, slot-die coating and spray coating as well as printing pathways such as screen, inkjet, and gravure printing besides vacuum deposition and laser patterning methods have been widely used as the substitutions of spin coating towards scaling up PSCs with a large area. In the current review, we have reported the practical potential of PSCs, strategies, challenges, and approaches towards the scaling up of large-area PSC modules via different deposition techniques as well as functional materials for the device architecture.